Join the growing community of curious minds on IDNLearn.com and get the answers you need. Our platform is designed to provide accurate and comprehensive answers to any questions you may have.
Sagot :
To determine the length of the longer leg [tex]\( I \)[/tex] in terms of the hypotenuse [tex]\( h \)[/tex], follow these steps:
1. Understand the problem: We know the hypotenuse ([tex]\( h \)[/tex]) is three times the shorter leg. Let’s denote the shorter leg as [tex]\( a \)[/tex].
2. Relation between hypotenuse and shorter leg: Given that [tex]\( h = 3a \)[/tex].
3. Apply the Pythagorean theorem: According to the theorem, for a right triangle:
[tex]\[ h^2 = a^2 + l^2 \][/tex]
where [tex]\( l \)[/tex] is the longer leg.
4. Substitute the hypotenuse:
[tex]\[ (3a)^2 = a^2 + l^2 \][/tex]
which simplifies to:
[tex]\[ 9a^2 = a^2 + l^2 \][/tex]
5. Solve for [tex]\( l^2 \)[/tex]:
[tex]\[ l^2 = 9a^2 - a^2 = 8a^2 \][/tex]
6. Express [tex]\( l \)[/tex] in terms of [tex]\( a \)[/tex]:
[tex]\[ l = \sqrt{8a^2} = \sqrt{8} \cdot a = 2\sqrt{2} \cdot a \][/tex]
7. Substitute [tex]\( a \)[/tex] in terms of [tex]\( h \)[/tex]: Since [tex]\( a = \frac{h}{3} \)[/tex], substitute this into the expression for [tex]\( l \)[/tex]:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
8. Simplify the expression:
[tex]\[ l = \frac{2\sqrt{2} \cdot h}{3} \][/tex]
Thus, the length of the longer leg [tex]\( I \)[/tex] can be written as:
[tex]\[ I = \frac{2\sqrt{2}h}{3} \][/tex]
In the format [tex]\( I = \frac{a \sqrt{b} h}{c} \)[/tex], the values are:
[tex]\[ a = 2, \quad b = 2, \quad c = 3 \][/tex]
So the final answer is:
[tex]\[ I = \frac{2 \sqrt{2} h}{3} \][/tex]
1. Understand the problem: We know the hypotenuse ([tex]\( h \)[/tex]) is three times the shorter leg. Let’s denote the shorter leg as [tex]\( a \)[/tex].
2. Relation between hypotenuse and shorter leg: Given that [tex]\( h = 3a \)[/tex].
3. Apply the Pythagorean theorem: According to the theorem, for a right triangle:
[tex]\[ h^2 = a^2 + l^2 \][/tex]
where [tex]\( l \)[/tex] is the longer leg.
4. Substitute the hypotenuse:
[tex]\[ (3a)^2 = a^2 + l^2 \][/tex]
which simplifies to:
[tex]\[ 9a^2 = a^2 + l^2 \][/tex]
5. Solve for [tex]\( l^2 \)[/tex]:
[tex]\[ l^2 = 9a^2 - a^2 = 8a^2 \][/tex]
6. Express [tex]\( l \)[/tex] in terms of [tex]\( a \)[/tex]:
[tex]\[ l = \sqrt{8a^2} = \sqrt{8} \cdot a = 2\sqrt{2} \cdot a \][/tex]
7. Substitute [tex]\( a \)[/tex] in terms of [tex]\( h \)[/tex]: Since [tex]\( a = \frac{h}{3} \)[/tex], substitute this into the expression for [tex]\( l \)[/tex]:
[tex]\[ l = 2\sqrt{2} \cdot \frac{h}{3} \][/tex]
8. Simplify the expression:
[tex]\[ l = \frac{2\sqrt{2} \cdot h}{3} \][/tex]
Thus, the length of the longer leg [tex]\( I \)[/tex] can be written as:
[tex]\[ I = \frac{2\sqrt{2}h}{3} \][/tex]
In the format [tex]\( I = \frac{a \sqrt{b} h}{c} \)[/tex], the values are:
[tex]\[ a = 2, \quad b = 2, \quad c = 3 \][/tex]
So the final answer is:
[tex]\[ I = \frac{2 \sqrt{2} h}{3} \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.